EXPERIMENTAL STUDY CONCERNING MASS TRANSFER INSIDE THE PACKED COLUMN OF SOLAR COOLING LIQUID DESICCANT SYSTEM USING COUNTER FLOW CONFIGURATION - R. Hengki Rahmanto (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2015)
Desiccant systems have been proposed as energy saving alternatives to vapor compression airconditioning for handling the latent load. Use of liquid desiccants offers several design and performanceadvantages over solid desiccants, especially when solar energy is used for regeneration. The liquid desiccantscontact the gas inside the packed column and the heat transfer and mass transfer will occur. This proposal istrying to study the mass transfer and heat transfer inside the packed column of dehumidifier and regeneratorsystems. And later on, the rates of dehumidification and regeneration that were affected by desiccant flow rates,air temperature and humidity, and desiccant temperature and all that variation will influence the performance ofthe systems.